Ethics: a problem for odontologists - Triana Estrada, Jorge (Acta Bioethica, 2006)
This work pretends to awake consciousness, both in health professionals and in odontology teaching institutions, about the risk of loss of credibility facing professional practice. It also aims to inform about the main causes of patients' disagreement due to the absence of ethical rules.